2018
DOI: 10.3389/fphar.2018.01317
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of CYP2E1 in the Course of Brain Edema Induced by Subacute Poisoning With 1,2-Dichloroethane in Mice

Abstract: This study was designed to explore the role of cytochrome P4502E1 (CYP2E1) expression in the course of brain edema induced by subacute poisoning with 1,2-dichloroethane (1,2-DCE). Mice were randomly divided into five groups: the control group, the 1,2-DCE poisoned group, and the low-, medium- and high-dose diallyl sulfide (DAS) intervention groups. The present study found that CYP2E1 expression levels in the brains of the 1,2-DCE-poisoned group were upregulated transcriptionally; in contrast, the levels were s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 43 publications
1
3
0
Order By: Relevance
“…Consistent with our previous studies [7,25], brain edema formed in the brain of mice in the 1,2 DCE-intoxicated group, which was indicated by increased brain water content and morphological changes of brain edema (Figure 1A,B). Moreover, compared with the control group, NF-κB binding activities in the brain of mice increased dramatically in the intoxicated group (Figure 1C), suggesting that NF-κB was activated during the course of 1,2-DCE-induced brain edema.…”
Section: Resultssupporting
confidence: 92%
“…Consistent with our previous studies [7,25], brain edema formed in the brain of mice in the 1,2 DCE-intoxicated group, which was indicated by increased brain water content and morphological changes of brain edema (Figure 1A,B). Moreover, compared with the control group, NF-κB binding activities in the brain of mice increased dramatically in the intoxicated group (Figure 1C), suggesting that NF-κB was activated during the course of 1,2-DCE-induced brain edema.…”
Section: Resultssupporting
confidence: 92%
“…CYP2E1 is the main enzyme that is implicated in 1,2-DCE metabolism in vivo [33]. Although its expression in the brain is much lower than in the liver, the enzyme is highly concentrated and inducible in the cortical astrocytes [34][35][36][37].…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that CYP2E1 can convert 1,2-DCE into 2-CE, chloroacetaldehyde and chloroacetic acid [38][39][40][41]. Because of the high oxidase activity, CYP2E1-mediated metabolism of 1,2-DCE and its intermediates can lead to the generation of ROS, as a consequence induce oxidative damage in the brain [20,33] The present results revealed that CYP2E1 knockdown reversed 2-CE-induced augmentation of ROS production and A1s induction, suggesting that ROS production is involved in A1 activation. Using the ROS scavenger NAC, we further determined that ROS induce A1s.…”
Section: Discussionmentioning
confidence: 99%